Geo-archaeological records of large Holocene tsunamis along the hyperarid coastal Atacama Desert in the major northern Chile seismic gap. (15th September 2019) - León, Tomás; Vargas, Gabriel; Salazar, Diego; Goff, James; Guendon, Jean Louis; Andrade, Pedro; Alvarez, Gabriel
Abstract: The coastal Atacama Desert is exposed to strong earthquakes and giant tsunamis associated with the subduction of the Nazca plate beneath the South American plate. Nevertheless, historical and geological records of tsunamis and paleotsunamis in this region are scarce. Taltal (25.4°S) is located at the southern edge of the hyperarid Atacama Desert within a major historical ∼1000 km-long megathrust seismic gap in northern Chile where the most recent large tsunamigenic earthquakes occurred in 1877 CE and 1922 CE, rupturing its northern and southern segments, respectively. By multiproxy geological and archaeological analyses from pits and trenches, we report distinctive strata of reworked archaeological material as well as sedimentary layers that we interpret as being produced by tsunami run-up and/or backwash deposition. We identified two large Holocene paleotsunamis dated close to ∼4000 cal yrs BP and younger than 863 ± 199 CE (∼1087 cal years BP). By comparing the run-ups of the last historical tsunamis with our minimum run-up estimates from the geo-archaeological record, we conclude that the impact of these Holocene paleotsunamis was larger than any known historical event, suggesting the need to re-evaluate local, regional and Pacific basin-scale tsunami hazard assessments. Highlights: First report of Holocene paleotsunami deposits in the hyperarid Atacama Desert. We document two large Holocene paleotsunamis in the northern Chile seismic gap. We reanalyzed the last large historical tsunamis in northern Chile. We suggest a re-assessment of the Pacific-wide tsunami hazard.